Impact of gadget use on the social behavior of elementary school children: A literature review - Kbarek, Yuliana Ida; Gurning, Maylar; Mannopposem, Inggerid A (Indonesian Journal of Health Services, 2025)
Background: Rapid technological development has increased gadget use among elementary school children, raising concerns regarding its influence on social behavior and developmental outcomes. Objective: This study aimed to analyze the impact of gadget use on the social behavior of elementary school children through a literature review approach. Methods: This study employed a literature review design following PRISMA guidelines to synthesize evidence from scientific publications. The literature search was conducted using the Google Scholar database with keywords related to gadget use, elementary school children, and learning outcomes. The search was limited to articles published between 2019 and 2024. Ten relevant studies that met the inclusion criteria were selected and analyzed through narrative synthesis to identify patterns and key findings related to gadget use and children's social behavior. Results: The results indicate that gadget use among elementary school children produces both positive and negative effects on social behavior. Excessive screen exposure tends to reduce children's direct social interaction and may contribute to behavioral dependency. Several studies show that prolonged gadget use may also influence children's emotional regulation, attention, and physical activity. However, controlled gadget use under parental supervision may support learning activities, information access, and digital literacy development. Parental involvement and balanced usage patterns play an important role in minimizing negative impacts and supporting children's social development. Conclusion: Gadget use significantly influences the social behavior of elementary school children depending on the duration of use, parental supervision, and usage context. Balanced digital media exposure combined with parental guidance may help optimize children's social and developmental outcomes.